Effects of Poly(ethylene-co-glycidyl methacrylate) on the Microstructure, Thermal, Rheological, and Mechanical Properties of Thermotropic Liquid Crystalline Polyester Blends - Lee, Sang Hoon (Polymers (Basel), 2020)
In this study, a series of thermotropic liquid crystalline polyester (TLCP)-based blends containing 1–30 wt% poly(ethylene-co-glycidyl methacrylate) (PEGMA) were fabricated by masterbatch-assisted melt-compounding. The scanning electron microscopy (SEM) images showed a uniformly dispersed microfibrillar structure for the TLCP component in cryogenically-fractured blends, without any phase-separated domains. The FT-IR spectra showed that the carbonyl stretching bands of TLCP/PEGMA blends shifted to higher wavenumbers, suggesting the presence of specific interactions and/or grafting reactions between carboxyl/hydroxyl groups of TLCP and glycidyl methacrylate groups of PEGMA. Accordingly, the melting and crystallization temperatures of the PEGMA component in the blends were greatly lowered compared to the TLCP component. The thermal decomposition peak temperatures of the PEGMA and TLCP components in the blends were characterized as higher than those of neat PEGMA and neat TLCP, respectively. From the rheological data collected at 300 °C, the shear moduli and complex viscosities for the blend with 30 wt% PEGMA were found to be much higher than those of neat PEGMA, which supports the existence of PEGMA-g-TLCP formed during the melt-compounding. The dynamic mechanical thermal analysis (DMA) analyses demonstrated that the storage moduli of the blends decreased slightly with the PEGMA content up to 3 wt%, increased at the PEGMA content of 5 wt%, and decreased again at PEGMA contents above 7 wt%. The maximum storage moduli for the blend with 5 wt% PEGMA are interpreted to be due to the reinforcing effect of PEGMA-g-TLCP copolymers.